Analysis and Optimization of Renewable Energy Integration in Microgrid Systems - Souf Omran Abdalslam; Alshibani Alhussein Zargoun (African Journal of Advanced Pure and Applied Sciences, 2024)
The integration of renewable energy into microgrid systems represents both a revolutionary shift and a formidable challenge in the quest for sustainable, resilient energy networks. Microgrids, with their capacity for localized energy generation, offer a pathway to reduce dependency on centralized grids, thus lowering emissions and fostering energy security. However, renewable sources like solar and wind, while essential to this vision, bring inherent unpredictability. This study dives deep into these complexities, exploring innovative optimization techniques designed to enhance renewable energy integration in microgrid systems. Through a combination of analytical methods and real-world case studies, this paper investigates solutions that address the fluctuating nature of renewables, ensuring stability, efficiency, and cost-effectiveness. We examine both classical optimization approaches and cutting-edge machine learning algorithms, assessing their effectiveness in improving grid reliability and reducing energy costs. Our findings reveal that tailored optimization strategies can transform microgrids, balancing sustainability with robust performance. Ultimately, this work provides a roadmap for future research, pointing to advancements that could redefine microgrid technology and accelerate the transition to greener energy infrastructures.